2021
DOI: 10.1116/6.0000774
|View full text |Cite
|
Sign up to set email alerts
|

Interface structure and luminescence properties of epitaxial PbSe films on InAs(111)A

Abstract: Epitaxial heterostructures of narrow-gap IV-VI and III-V semiconductors offer a platform for new electronics and mid-infrared photonics. Stark dissimilarities in the bonding and the crystal structure between the rocksalt IV–VIs and the zincblende III–Vs, however, mandate the development of nucleation and growth protocols to reliably prepare high-quality heterostructures. In this work, we demonstrate a route to single crystal (111)-oriented PbSe epitaxial films on nearly lattice-matched InAs (111)A templates. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 61 publications
2
13
0
Order By: Relevance
“…The fourth strategy we tried is predose treatment of the substrate. It has been shown that by exposing the substrate to the material flux above the thermal decomposition temperature, single crystal (111)-oriented PbSe can be epitaxially grown on nearly lattice-matched InAs (111) A templates . Twin formation has been suppressed by a predose of the epitaxy material.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fourth strategy we tried is predose treatment of the substrate. It has been shown that by exposing the substrate to the material flux above the thermal decomposition temperature, single crystal (111)-oriented PbSe can be epitaxially grown on nearly lattice-matched InAs (111) A templates . Twin formation has been suppressed by a predose of the epitaxy material.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that by exposing the substrate to the material flux above the thermal decomposition temperature, single crystal (111)-oriented PbSe can be epitaxially grown on nearly lattice-matched InAs (111) A templates. 71 Twin formation has been suppressed by a predose of the epitaxy material. A similar method of predosing the substrate with Bi 2 Se 3 has been tried on sapphire: a bismuth predose of 2 min at a low temperature is used followed by growth of a buffer layer of Bi 2 Se 3 , which is then re-evaporated in a flash heat up process.…”
Section: Resultsmentioning
confidence: 99%
“…3 Furthermore, epitaxial heterostructures of narrow-gap IV-VI and III-V semiconductors are a promising candidate for mid-infrared photonics, where the main benefits are the lattice constant matching, mechanical strength, chemical stability, and thermal conductivity as compared to the currently used substrates. 4 InAs is also the compound semiconductor of choice for building a hybrid semiconductor-superconductor based topological quantum bit, due to its unique combination of electronic properties such as e.g. large spin-orbit interaction and a narrow direct bandgap.…”
Section: Introductionmentioning
confidence: 99%
“…3 Furthermore, epitaxial heterostructures of narrow-gap IV−VI and III−V semiconductors are a promising candidate for midinfrared photonics, where the main benefits are the lattice constant matching, mechanical strength, chemical stability, and thermal conductivity as compared to the currently used substrates. 4 InAs is also the compound semiconductor of choice for building a hybrid semiconductor−superconductorbased topological quantum bit, due to its unique combination of electronic properties such as, e.g., large spin−orbit interaction and a narrow direct bandgap. 5 InAs(111) forms a low strain interface with GaSb and AlSb, other technologically relevant III−V compound semiconductors, as well as several II−VI compound semiconductors.…”
Section: ■ Introductionmentioning
confidence: 99%